Seroprevalence of foot and mouth disease and peste des petits ruminants in small ruminants in Zambia on the border to Tanzania : Searching for common traits among seropositive herds - Mitternacht, Lydia (SLU/Dept. of Clinical Sciences (until 231231), 2019)
Foot and mouth disease (FMD) and peste des petits ruminants (PPR) are highly contagious viral diseases affecting sheep and goats all over the world. Small ruminants are often owned by poor small-scale farmers in the developing world, and several studies have identified them to be among the most important livestock species for the poor. Controlling, or even eradicating, FMD and PPR is important for alleviating poverty. More than half of Zambia’s population was living below the national poverty line in 2015. FMD is today considered to be endemic in Zambia, the most recent outbreak was in March 2018. No clinical cases of PPR have been found within the country so far but PPR is highly present in Zambia’s bordering countries in the north and Zambia is therefore under constant risk of the incursion of PPR.